Exploring the past through relics: the Oxford Relics Research Cluster - Georges Kazan (Taylor & Francis, 2022)
The Oxford Relics Cluster, of which the author is co-director, is a group of scholars from traditionally distinct subjects, including history, history of art, archaeology, and theology, as well as other scientific disciplines (e.g. medicine, computer science), seeking to realize the major research opportunities presented by relics for improving our understanding of our human past, and its ramifications for today’s world. This article sets out the background and outlook for the new field of interdisciplinary relic studies and summarises the Cluster's aims and activities.